ADVANCED MATERIALS AND NANOTECHNOLOGY IN ENGINEERING APPLICATIONS (International journal of artificial intelligence, 2026)
Advanced materials and nanotechnology have significantly transformed modern engineering by enabling the development of high-performance, lightweight, and multifunctional systems. Materials engineered at the micro- and nanoscale exhibit enhanced mechanical, electrical, thermal, and chemical properties. This article explores the role of advanced materials and nanotechnology in engineering applications, highlighting key material classes, fabrication techniques, practical implementations, challenges, and future prospects.